Bumpy Topographic Effects on the Transbasin Evolution of Large‐Amplitude Internal Solitary Wave in the Northern South China Sea. Issue 7 (9th July 2019) - Xie, Jieshuo; He, Yinghui; Cai, Shuqun
Abstract: The bumpy continental slope/shelf topography is a quite common feature in the northern South China Sea (SCS), yet its effect on the shoaling internal solitary waves (ISWs) remains poorly understood. Therefore, numerical simulations by a fully nonlinear, nonhydrostatic model are carried out to explore the bumpy continental slope/shelf topographic effects on the transbasin evolution of large‐amplitude ISW in the northern SCS. It is found that the prominent bumps over both continental slope and shelf regions play significant roles in modulating the evolution of transbasin ISW in the northern SCS. The bump over the continental slope is capable of triggering a solitary‐like mode‐2 internal wave packet, while the bump over the continental shelf can result in three wave groups, including a leading group of rank‐ordered mode‐1 ISW packet and two following groups of non‐rank‐ordered mode‐1 ISW packet and mode‐2 internal waves. The bumps can cause a peak‐to‐peak difference of the energy decay rate of ISW up to 10–20 kW/m over continental slope region and 3–5 kW/m over continental shelf region. The wave kinetic energy (KE) is found to exceed the available potential energy (APE) by as much as 50% over the continental shelf break region. Over the shelf region, however, the bumps can first make the KE drop to as low as only 80% of the APE, but later the KE might bounce back to approximately 1.1–1.2 times of the APE. Both onshore‐ and offshore‐propagating beam‐like disturbances are found to be excited by the bumps. Except for the onshore‐propagating mode‐2 ISW packet, the reflected offshore‐propagating waves in different internal modes are also formed. These onshore‐ and offshore‐propagating multimodal internal waves can be clarified by the beam scattering and local generation mechanism. Key Points: Bumpy continental slope/shelf topographic effects on transbasin ISW in northern SCS are studied using fully nonlinear, nonhydrostatic model Transformation and energy decay and partition of transbasin ISW vary greatly due to complexity of realistic bumpy topography in northern SCS Both onshore‐ and offshore‐propagating multimodal waves are triggered and can be clarified by beam scattering and local generation mechanism